D. W. Winnicott, transitional objects, and the importance of materialization for religious belief - Gabel, Stewart (Journal of spirituality in mental health, 2019)
Idols, icons and religious images have had an enormous influence on the spiritual and religious lives of individuals and communities for millennia. This paper explores aspects of this attraction from a psychological perspective using the model of transitional objects developed by D. W. Winnicott, a 20th century British psychoanalyst. I argue that the worship or veneration of material forms may at times represent or symbolize the unseen divinity or god for the believer, but at times these forms may also "be" the divine or be considered an aspect of the divine in material form, thus facilitating religious devotion.